Mental maps and representations of the city centre of Thessaloniki - Olympia PAPAIOANNOU; Apostolos PAPAGIANNAKIS; Panagiotis A. HATZIPROKOPIOU (European Journal of Geography)
Mental maps are the type of maps that everyone creates in their minds to orient themselves in space. The orienting process takes place on a daily basis, mostly unconsciously. Even the citizens of the same city tend to perceive urban space differently, emphasizing on different parts of the city, as their perceptions reflect their lifestyle, habits, preferences, experiences, but mostly the feelings that the space itself provokes to them. Human-centered factors, such as mental capacity, memories, emotional state, age, gender, as well as social-cultural ones, such as social media influences and prejudices, have a great significance on mental mapping. Inspired by Kevin Lynch (1960) and Jack Nasar (1990), this paper analyzes the center of Thessaloniki, through information and mental maps gathered from 50 interviews with residents, both men and women from different age groups and a range of social classes. The analysis traces the features that attract (e.g. the water element) or repel (e.g. the presence of marginalized groups) the inhabitants of Thessaloniki, their feelings (e.g. insecurity) and the daily routes they follow for various activities. It attempts to identify their common but also different perceptions of the city, the stereotypes, prejudices and their origins. However, the most important role seems to be played by the experiences that each person has lived in specific places. Finally, apart from being unique products that reveal each person’s intimate thoughts about spa